A modified cemented carbide tool and preparation method thereof
By using WC powder, Co powder, Ni powder and Cr3C2 matrix materials in cemented carbide tools, combined with stearic acid, paraffin and ethanol additives, ball milling and sintering improved treatment, combined with modification additives and mixing liquid, the solution was solved Carbide tools achieve coordinated performance improvement and stability improvement in impact toughness, bending strength and cold-heat resistance.
Patent Information
- Application Number
- CN202411455401.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing cemented carbide tools are difficult to balance impact toughness, fracture toughness and flexural strength, and have poor stability under cold-heat resistance and high corrosion resistance conditions, which limits their use efficiency.
WC powder, Co powder, Ni powder and Cr3C2 are used as matrix materials, stearic acid, paraffin and ethanol are added as additives, and the treatment is improved by ball milling, pressing molding and sintering, and modified additives and mixing liquids, and fractionation is adopted. The thermal sintering and spraying of the mixing fluid treatment of the segments are blended to improve performance.
The balance of fracture toughness, impact toughness and bending strength of cemented carbide tools is significantly improved, and the performance stability under cold-heat resistance and high corrosion resistance conditions is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cemented carbide cutting tools, and in particular to a modified cemented carbide cutting tool and a preparation method thereof. Background Art
[0002] Cemented carbide is widely used in cutting of various metal materials, and is also suitable for coal mining, geological exploration, mining drills, cone drill teeth, stretching and stamping dies, etc. It is widely used in machinery, chemical industry, petroleum, metallurgy, electronics, national defense and other fields. However, when existing cemented carbide is used on cutting tools, the impact toughness of cemented carbide products is poor, and it is difficult to improve the fracture toughness, impact toughness and bending strength of the products. It is a technical difficulty to balance and improve the performance of the products. At the same time, the product has poor stability under the conditions of cold-heat resistance and high corrosion resistance, which limits the use efficiency of the products. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a modified cemented carbide tool and a preparation method thereof to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a method for preparing a modified cemented carbide tool, comprising the following steps:
[0006] Step 1: weigh the raw materials of the alloy tool according to weight:
[0007] 70-75 parts WC powder, 5-10 parts Co powder, 2-5 parts Ni powder, 2-4 parts Cr 3 C 2 , 4-7 parts of stearic acid, 8-12 parts of paraffin wax and 35-40 parts of ethanol solvent and 4-7 parts of modifying additives;
[0008] Step 2, the raw materials of step 1 are mixed thoroughly, and then ball milled at a ball milling speed of 1000-1500r / min for 2h, and the ball milling is completed to obtain a ball milled material;
[0009] Step 3: The ball mill is dried and passed through a 100-mesh sieve, and then pressed in a mold to obtain a green body, and then the green body is sprayed with the conditioning liquid until the green body is wetted;
[0010] Step 4: sintering the product of step 3 to improve the process, and after sintering, the modified cemented carbide tool of the present invention is obtained.
[0011] Preferably, the pressing pressure is 100-150 MPa, and the pressing time is 20-30 min;
[0012] The specific sintering steps of the sintering improvement treatment are:
[0013] First, keep the temperature at 70-75℃ for 40-50min, then increase the temperature to 450-470℃ at a rate of 2-5℃ / min and keep it for 2-4h;
[0014] Then heat up to 1050-1100℃ at a rate of 4-7℃ / min, keep warm for 2-3h, then heat up to 1350℃ at a rate of 1-3℃ / min, keep warm for 30-40min, and finally air cool to room temperature.
[0015] Preferably, the preparation method of the modified additive is:
[0016] S11: uniformly dispersing the carbon nanotubes in a sufficient amount of 5-7% potassium permanganate solution by ultrasonication at an ultrasonic power of 350-400 W for 20 min, then repeatedly washing with boiling water for 3 times, then filtering and drying;
[0017] S12: 3-5 parts of sodium alginate powder, 4-7 parts of lanthanum chloride solution and 1-2 parts of phosphate buffer solution are mixed together to obtain a sodium alginate solution;
[0018] The carbon nanotubes dried in S11 and the sodium alginate solution were stirred at a weight ratio of 2:5, and after the stirring was completed, the mixture was filtered and dried to obtain a carbon nanotube and sodium alginate agent;
[0019] S13: Mix the carbon nanotubes, sodium alginate agent and the additive liquid doped with titanium diboride in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1000-1500 r / min for 2 hours. After the ball milling is completed, wash with water and dry to obtain a modified additive.
[0020] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%; and the pH value of the phosphate buffer solution is 5.5.
[0021] Preferably, the stirring speed of the stirring treatment in S12 is 450-550 r / min, the stirring time is 20-30 min, and the stirring temperature is 50-55°C.
[0022] Preferably, the preparation method of the additive solution doped with titanium diboride is:
[0023] Titanium diboride, sodium silicate solution and citric acid are mixed in a weight ratio of (3-4): (5-7): 1, and the mixture is ball-milled thoroughly at a speed of 1500 r / min for 1 h to obtain titanium diboride liquid;
[0024] The nano-neodymium oxide is immersed in a chitosan solution which is 3-5 times the total amount of the nano-neodymium oxide and stirred sufficiently. After the immersion and stirring are completed, the modified nano-neodymium oxide is obtained. The titanium diboride liquid and the modified nano-neodymium oxide are further mixed and stirred in a weight ratio of 4:3 to obtain an additive solution doped with titanium diboride.
[0025] Preferably, the mass fraction of the sodium silicate solution is 3-5%; the mass fraction of the chitosan solution is 2-4%;
[0026] The stirring speed for sufficient immersion stirring is 750-850r / min, and the stirring time is 20-30min; the stirring speed for sufficient mixing stirring is 550-650r / min, and the stirring time is 45-55min.
[0027] Preferably, the preparation method of the conditioning liquid is:
[0028] S101: irradiating the nano-flaky aluminum oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350 W, and obtaining a nano-flaky aluminum oxide agent after the irradiation is completed;
[0029] S102: 4-7 parts of nano-flaky alumina agent, 3-5 parts of silane coupling agent, 1-3 parts of 5% by mass sodium dodecylbenzene sulfonate solution and 6-8 parts of 2-4% by mass yttrium nitrate solution are mixed to obtain a performance adjustment solution.
[0030] Preferably, the silane coupling agent is silane coupling agent KH560.
[0031] The invention also provides a modified cemented carbide tool prepared by a method for preparing the modified cemented carbide tool.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The cemented carbide tool of the present invention adopts WC powder, Co powder, Ni powder and Cr 3 C 2 The base material is stearic acid, paraffin and ethanol as additives, and the modified additives are added as synergistic agents. The hard alloy tool products are obtained by ball milling, pressing, spraying the effect-adjusting liquid and sintering improvement treatment. The fracture toughness, impact toughness and bending strength of the products are balanced and coordinated, and the product performance stability is remarkable under the conditions of cold-heat resistance and high corrosion resistance.
[0034] 2. Sintering improvement treatment: Preheat treatment is carried out at 70-75℃, and then the temperature is increased to 450-470℃ at a rate of 2-5℃ / min, and the temperature is kept for 2-4h; then the temperature is increased to 1050-1100℃ at a rate of 4-7℃ / min, and the temperature is kept for 2-3h, and then the temperature is increased to 1350℃ at a rate of 1-3℃ / min, and the temperature is kept for 30-40min. Through the graded and segmented thermal sintering improvement, and the change efficiency of the heating rate from low-high-low, the product is sintered thoroughly and the grain is fully refined. Then, the spraying of the effect-adjusting liquid and the modified additives are coordinated and synergistic, so that the performance of the product is further improved;
[0035] 3. The modified additive adopts carbon nanotubes treated with potassium permanganate solution to optimize the activity efficiency of carbon nanotubes, and then sodium alginate solution is prepared by co-preparing with sodium alginate powder, lanthanum chloride solution and phosphate buffer solution. The sodium alginate solution and carbon nanotubes are stirred and treated to coordinate and coordinate the carbon nanotubes with high specific surface area in the sodium alginate solution, and the additive solution doped with titanium diboride is prepared by mixing titanium diboride, sodium silicate solution and citric acid, and then the modified nano-neodymium oxide prepared by nano-neodymium oxide and chitosan solution is coordinated and enhanced, and titanium diboride is doped in the system to enhance the performance coordination of the system. At the same time, the additive solution doped with titanium diboride is coordinated with carbon nanotubes and sodium alginate agent to coordinate and enhance the performance, so that the performance of the product in the modified additive system is further improved;
[0036] 4. The conditioning liquid uses nano-flaky alumina that has been irradiated with protons to stimulate its active efficiency, and then it is mixed and blended with a silane coupling agent, a 5% by mass sodium dodecylbenzene sulfonate solution, and a 2-4% by mass yttrium nitrate solution. Through the blending and deployment of the raw materials, the nano-flaky alumina is used as the matrix and is more strongly attached to the surface of the green body. The raw materials in the conditioning liquid are blended to enhance the interface of the system, and then the sintering is improved in coordination, the grains are better refined, and the grain structure is activated and enhanced, so that the performance of the product is further improved. DETAILED DESCRIPTION
[0037] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] A method for preparing a modified cemented carbide tool in this embodiment comprises the following steps:
[0039] Step 1: weigh the raw materials of the alloy tool according to weight:
[0040] 70-75 parts WC powder, 5-10 parts Co powder, 2-5 parts Ni powder, 2-4 parts Cr 3 C 2 , 4-7 parts of stearic acid, 8-12 parts of paraffin wax and 35-40 parts of ethanol solvent and 4-7 parts of modifying additives;
[0041] Step 2, the raw materials of step 1 are mixed thoroughly, and then ball milled at a ball milling speed of 1000-1500r / min for 2h, and the ball milling is completed to obtain a ball milled material;
[0042] Step 3: The ball mill is dried and passed through a 100-mesh sieve, and then pressed in a mold to obtain a green body, and then the green body is sprayed with the conditioning liquid until the green body is wetted;
[0043] Step 4: sintering the product of step 3 to improve the process, and after sintering, the modified cemented carbide tool of the present invention is obtained.
[0044] The pressing pressure of this embodiment is 100-150MPa, and the pressing time is 20-30min;
[0045] The specific sintering steps of the sintering improvement treatment are:
[0046] First, keep the temperature at 70-75℃ for 40-50min, then increase the temperature to 450-470℃ at a rate of 2-5℃ / min and keep it for 2-4h;
[0047] Then heat up to 1050-1100℃ at a rate of 4-7℃ / min, keep warm for 2-3h, then heat up to 1350℃ at a rate of 1-3℃ / min, keep warm for 30-40min, and finally air cool to room temperature.
[0048] The preparation method of the modified additive of this embodiment is:
[0049] S11: uniformly dispersing the carbon nanotubes in a sufficient amount of 5-7% potassium permanganate solution by ultrasonication at an ultrasonic power of 350-400 W for 20 min, then repeatedly washing with boiling water for 3 times, then filtering and drying;
[0050] S12: 3-5 parts of sodium alginate powder, 4-7 parts of lanthanum chloride solution and 1-2 parts of phosphate buffer solution are mixed together to obtain a sodium alginate solution;
[0051] The carbon nanotubes dried in S11 and the sodium alginate solution were stirred at a weight ratio of 2:5, and after the stirring was completed, the mixture was filtered and dried to obtain a carbon nanotube and sodium alginate agent;
[0052] S13: Mix the carbon nanotubes, sodium alginate agent and the additive liquid doped with titanium diboride in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1000-1500 r / min for 2 hours. After the ball milling is completed, wash with water and dry to obtain a modified additive.
[0053] The mass fraction of the lanthanum chloride solution of this embodiment is 2-5%; the pH value of the phosphate buffer solution is 5.5.
[0054] The stirring speed of the stirring treatment in S12 of this embodiment is 450-550 r / min, stirring for 20-30 min, and stirring temperature is 50-55°C.
[0055] The preparation method of the additive solution doped with titanium diboride in this embodiment is as follows:
[0056] Titanium diboride, sodium silicate solution and citric acid are mixed in a weight ratio of (3-4): (5-7): 1, and the mixture is ball-milled thoroughly at a speed of 1500 r / min for 1 h to obtain titanium diboride liquid;
[0057] The nano-neodymium oxide is immersed in a chitosan solution which is 3-5 times the total amount of the nano-neodymium oxide and stirred sufficiently. After the immersion and stirring are completed, the modified nano-neodymium oxide is obtained. The titanium diboride liquid and the modified nano-neodymium oxide are further mixed and stirred in a weight ratio of 4:3 to obtain an additive solution doped with titanium diboride.
[0058] The mass fraction of the sodium silicate solution in this embodiment is 3-5%; the mass fraction of the chitosan solution is 2-4%;
[0059] The stirring speed for sufficient immersion stirring is 750-850r / min, and the stirring time is 20-30min; the stirring speed for sufficient mixing stirring is 550-650r / min, and the stirring time is 45-55min.
[0060] The preparation method of the conditioning liquid of this embodiment is:
[0061] S101: irradiating the nano-flaky aluminum oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350 W, and obtaining a nano-flaky aluminum oxide agent after the irradiation is completed;
[0062] S102: 4-7 parts of nano-flaky alumina agent, 3-5 parts of silane coupling agent, 1-3 parts of 5% by mass sodium dodecylbenzene sulfonate solution and 6-8 parts of 2-4% by mass yttrium nitrate solution are mixed to obtain a performance adjustment solution.
[0063] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0064] The modified cemented carbide tool is prepared by a method for preparing a modified cemented carbide tool in this embodiment.
[0065] Example 1.
[0066] A method for preparing a modified cemented carbide tool in this embodiment comprises the following steps:
[0067] Step 1: weigh the raw materials of the alloy tool according to weight:
[0068] 70 parts WC powder, 5 parts Co powder, 2 parts Ni powder, 2 parts Cr 3 C 2 , 4 parts of stearic acid, 8 parts of paraffin wax and 35 parts of ethanol solvent and 4 parts of modifying additives;
[0069] Step 2, the raw materials of step 1 are mixed thoroughly, and then ball milled at a ball milling speed of 1000r / min for 2h, and the ball milling is completed to obtain a ball milled material;
[0070] Step 3: The ball mill is dried and passed through a 100-mesh sieve, and then pressed in a mold to obtain a green body, and then the green body is sprayed with the conditioning liquid until the green body is wetted;
[0071] Step 4: sintering the product of step 3 to improve the process, and after sintering, the modified cemented carbide tool of the present invention is obtained.
[0072] The pressing pressure of this embodiment is 100MPa and the pressing time is 20min;
[0073] The specific sintering steps of the sintering improvement treatment are:
[0074] First, keep the temperature at 70℃ for 40min, then increase the temperature to 450℃ at a rate of 2℃ / min and keep it for 2h;
[0075] Then increase the temperature to 1050°C at a rate of 4°C / min, keep it at that temperature for 2h, then increase the temperature to 1350°C at a rate of 1°C / min, keep it at that temperature for 30min, and finally air cool to room temperature.
[0076] The preparation method of the modified additive of this embodiment is:
[0077] S11: The carbon nanotubes are first dispersed uniformly in a sufficient amount of 5% by mass potassium permanganate solution by ultrasonication at an ultrasonic power of 350 W for 20 min, and then washed repeatedly with boiling water for 3 times, and then filtered and dried;
[0078] S12: 3 parts of sodium alginate powder, 4 parts of lanthanum chloride solution and 1 part of phosphate buffer solution are mixed together to obtain a sodium alginate solution;
[0079] The carbon nanotubes dried in S11 and the sodium alginate solution were stirred at a weight ratio of 2:5, and after the stirring was completed, the mixture was filtered and dried to obtain a carbon nanotube and sodium alginate agent;
[0080] S13: Mix the carbon nanotubes, sodium alginate agent and the additive liquid doped with titanium diboride in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, wash with water and dry to obtain a modified additive.
[0081] The mass fraction of the lanthanum chloride solution of this embodiment is 2%; the pH value of the phosphate buffer solution is 5.5.
[0082] The stirring speed of the stirring treatment in S12 of this embodiment is 450 r / min, stirring for 20 min, and the stirring temperature is 50° C.
[0083] The preparation method of the additive solution doped with titanium diboride in this embodiment is as follows:
[0084] Titanium diboride, sodium silicate solution and citric acid were mixed in a weight ratio of 3:5:1 and ball-milled thoroughly at a ball-milling speed of 1500 r / min for 1 h to obtain titanium diboride liquid;
[0085] The nano-neodymium oxide is immersed in a chitosan solution that is 3 times the total amount of the nano-neodymium oxide, and the solution is stirred sufficiently. After the immersion and stirring are completed, the modified nano-neodymium oxide is obtained. The titanium diboride liquid and the modified nano-neodymium oxide are further mixed and stirred in a weight ratio of 4:3 to obtain an additive solution doped with titanium diboride.
[0086] The mass fraction of the sodium silicate solution in this embodiment is 3%; the mass fraction of the chitosan solution is 2%;
[0087] The stirring speed for sufficient immersion stirring is 75 r / min, and the stirring time is 20 min; the stirring speed for sufficient mixing stirring is 550 r / min, and the stirring time is 45 min.
[0088] The preparation method of the conditioning liquid of this embodiment is:
[0089] S101: irradiating the nano-flaky aluminum oxide in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining a nano-flaky aluminum oxide agent after the irradiation is completed;
[0090] S102: 4 parts of nano-flaky alumina agent, 3 parts of silane coupling agent, 1 part of 5% by mass sodium dodecylbenzene sulfonate solution and 6 parts of 2% by mass yttrium nitrate solution are mixed to obtain a performance adjustment solution.
[0091] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0092] The modified cemented carbide tool is prepared by a method for preparing a modified cemented carbide tool in this embodiment.
[0093] Example 2.
[0094] A method for preparing a modified cemented carbide tool in this embodiment comprises the following steps:
[0095] Step 1: weigh the raw materials of the alloy tool according to weight:
[0096] 75 parts WC powder, 10 parts Co powder, 5 parts Ni powder, 4 parts Cr 3 C 2 , 7 parts of stearic acid, 12 parts of paraffin wax and 40 parts of ethanol solvent and 7 parts of modifying additives;
[0097] Step 2, the raw materials of step 1 are mixed thoroughly, and then ball milled at a ball milling speed of 1500r / min for 2h, and the ball milling is completed to obtain a ball milled material;
[0098] Step 3: The ball mill is dried and passed through a 100-mesh sieve, and then pressed in a mold to obtain a green body, and then the green body is sprayed with the conditioning liquid until the green body is wetted;
[0099] Step 4: sintering the product of step 3 to improve the process, and after sintering, the modified cemented carbide tool of the present invention is obtained.
[0100] The pressing pressure of this embodiment is 150MPa and the pressing time is 30min;
[0101] The specific sintering steps of the sintering improvement treatment are:
[0102] First, keep the temperature at 75℃ for 50min, then increase the temperature to 470℃ at a rate of 5℃ / min and keep it for 4h;
[0103] Then increase the temperature to 1100°C at a rate of 7°C / min, keep it at that temperature for 3h, then increase the temperature to 1350°C at a rate of 3°C / min, keep it at that temperature for 40min, and finally air cool to room temperature.
[0104] The preparation method of the modified additive of this embodiment is:
[0105] S11: The carbon nanotubes are first dispersed uniformly in a sufficient amount of 7% potassium permanganate solution by ultrasonication at an ultrasonic power of 400 W for 20 min, and then washed repeatedly with boiling water for 3 times, and then filtered and dried;
[0106] S12: 5 parts of sodium alginate powder, 7 parts of lanthanum chloride solution and 2 parts of phosphate buffer solution are mixed together to obtain a sodium alginate solution;
[0107] The carbon nanotubes dried in S11 and the sodium alginate solution were stirred at a weight ratio of 2:5, and after the stirring was completed, the mixture was filtered and dried to obtain a carbon nanotube and sodium alginate agent;
[0108] S13: Mix the carbon nanotubes, sodium alginate agent and the additive liquid doped with titanium diboride in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1500 r / min for 2 h. After the ball milling is completed, wash with water and dry to obtain a modified additive.
[0109] The mass fraction of the lanthanum chloride solution of this embodiment is 5%; the pH value of the phosphate buffer solution is 5.5.
[0110] The stirring speed of the stirring treatment in S12 of this embodiment is 550 r / min, stirring is 30 min, and the stirring temperature is 55°C.
[0111] The preparation method of the additive solution doped with titanium diboride in this embodiment is as follows:
[0112] Titanium diboride, sodium silicate solution and citric acid were mixed in a weight ratio of 4:7:1 and ball-milled thoroughly at a ball-milling speed of 1500 r / min for 1 h to obtain titanium diboride liquid;
[0113] The nano-neodymium oxide is immersed in a chitosan solution that is 5 times the total amount of the nano-neodymium oxide, and the solution is stirred sufficiently. After the immersion and stirring are completed, the modified nano-neodymium oxide is obtained. The titanium diboride liquid and the modified nano-neodymium oxide are further mixed and stirred in a weight ratio of 4:3 to obtain an additive solution doped with titanium diboride.
[0114] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the chitosan solution is 4%;
[0115] The stirring speed for sufficient immersion stirring is 850 r / min, and the stirring time is 30 min; the stirring speed for sufficient mixing stirring is 650 r / min, and the stirring time is 55 min.
[0116] The preparation method of the conditioning liquid of this embodiment is:
[0117] S101: irradiating the nano-flaky aluminum oxide in a proton irradiation box for 10 minutes at an irradiation power of 350 W, and obtaining a nano-flaky aluminum oxide agent after the irradiation is completed;
[0118] S102: 7 parts of nano-flaky alumina agent, 5 parts of silane coupling agent, 3 parts of 5% by mass sodium dodecylbenzene sulfonate solution and 8 parts of 4% by mass yttrium nitrate solution are mixed to obtain a conditioning solution.
[0119] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0120] The modified cemented carbide tool is prepared by a method for preparing a modified cemented carbide tool in this embodiment.
[0121] Example 3.
[0122] A method for preparing a modified cemented carbide tool in this embodiment comprises the following steps:
[0123] Step 1: weigh the raw materials of the alloy tool according to weight:
[0124] 72.5 parts WC powder, 7.5 parts Co powder, 3.5 parts Ni powder, 3 parts Cr 3 C 2 , 5.5 parts of stearic acid, 10 parts of paraffin wax and 37.5 parts of ethanol solvent and 5.5 parts of modifying additives;
[0125] Step 2, the raw materials of step 1 are mixed thoroughly, and then ball milled at a ball milling speed of 1250r / min for 2h, and the ball milling is completed to obtain a ball milled material;
[0126] Step 3: The ball mill is dried and passed through a 100-mesh sieve, and then pressed in a mold to obtain a green body, and then the green body is sprayed with the conditioning liquid until the green body is wetted;
[0127] Step 4: sintering the product of step 3 to improve the process, and after sintering, the modified cemented carbide tool of the present invention is obtained.
[0128] The pressing pressure of this embodiment is 125MPa and the pressing time is 25min;
[0129] The specific sintering steps of the sintering improvement treatment are:
[0130] First, keep the temperature at 72.5℃ for 45min, then increase the temperature to 460℃ at a rate of 3.5℃ / min and keep it for 3h;
[0131] Then increase the temperature to 1075°C at a rate of 5.5°C / min, keep it at that temperature for 2.5h, then increase the temperature to 1350°C at a rate of 2°C / min, keep it at that temperature for 35min, and finally air cool to room temperature.
[0132] The preparation method of the modified additive of this embodiment is:
[0133] S11: The carbon nanotubes are first dispersed uniformly in a sufficient amount of 6% potassium permanganate solution by ultrasonication at an ultrasonic power of 370 W for 20 min, and then washed repeatedly with boiling water for 3 times, and then filtered and dried;
[0134] S12: 4 parts of sodium alginate powder, 5.5 parts of lanthanum chloride solution and 1.5 parts of phosphate buffer solution are mixed together to obtain a sodium alginate solution;
[0135] The carbon nanotubes dried in S11 and the sodium alginate solution were stirred at a weight ratio of 2:5, and after the stirring was completed, the mixture was filtered and dried to obtain a carbon nanotube and sodium alginate agent;
[0136] S13: Mix the carbon nanotubes, sodium alginate agent and the additive liquid doped with titanium diboride in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1250 r / min for 2 h. After the ball milling is completed, wash with water and dry to obtain a modified additive.
[0137] The mass fraction of the lanthanum chloride solution of this embodiment is 3.5%; the pH value of the phosphate buffer solution is 5.5.
[0138] The stirring speed of the stirring treatment in S12 of this embodiment is 500 r / min, stirring is 25 min, and the stirring temperature is 52.5°C.
[0139] The preparation method of the additive solution doped with titanium diboride in this embodiment is as follows:
[0140] Titanium diboride, sodium silicate solution and citric acid were mixed and ball-milled in a weight ratio of 3.5:6:1 at a ball-milling speed of 1500 r / min for 1 h to obtain titanium diboride liquid;
[0141] The nano-neodymium oxide is immersed in a chitosan solution that is 4 times the total amount of the nano-neodymium oxide, and the solution is stirred sufficiently. After the immersion and stirring are completed, the modified nano-neodymium oxide is obtained. The titanium diboride liquid and the modified nano-neodymium oxide are further mixed and stirred in a weight ratio of 4:3 to obtain an additive solution doped with titanium diboride.
[0142] The mass fraction of the sodium silicate solution in this embodiment is 4%; the mass fraction of the chitosan solution is 3%;
[0143] The stirring speed for sufficient immersion stirring is 800 r / min, and the stirring time is 25 min; the stirring speed for sufficient mixing stirring is 60 r / min, and the stirring time is 50 min.
[0144] The preparation method of the conditioning liquid of this embodiment is:
[0145] S101: irradiating the nano-flaky aluminum oxide in a proton irradiation box for 7.5 minutes at an irradiation power of 350 W, and obtaining a nano-flaky aluminum oxide agent after the irradiation is completed;
[0146] S102: 5.5 parts of nano-flaky alumina agent, 4 parts of silane coupling agent, 2 parts of 5% by mass sodium dodecylbenzene sulfonate solution and 7 parts of 3% by mass yttrium nitrate solution are mixed to obtain a conditioning solution.
[0147] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0148] The modified cemented carbide tool is prepared by a method for preparing a modified cemented carbide tool in this embodiment.
[0149] Comparative Example 1.
[0150] The difference from Example 3 is that no modifying additive is added to the raw material of the alloy tool.
[0151] Comparative Example 2.
[0152] The difference from Example 3 is that the modified additive is not treated with sodium alginate solution.
[0153] Comparative Example 3.
[0154] The difference from Example 3 is that the sodium alginate solution is replaced by a sodium alginate solution with a mass fraction of 5%.
[0155] Comparative Example 4.
[0156] The difference from Example 3 is that no S11-dried carbon nanotubes are added to the modified additive.
[0157] Comparative Example 5.
[0158] The difference from Example 3 is that no additive liquid for doping titanium diboride is added to the modified additive.
[0159] Comparative Example 6.
[0160] The difference from Example 3 is that no conditioning liquid treatment was used.
[0161] Comparative Example 7.
[0162] The difference from Example 3 is that no nano-flaky alumina agent is added to the conditioning solution.
[0163] Comparative Example 8.
[0164] The difference from Example 3 is that no yttrium nitrate solution and silane coupling agent are added to the conditioning solution.
[0165] Comparative Example 9.
[0166] The difference from Example 3 is that the specific operation of the sintering improvement treatment is different:
[0167] The specific sintering steps are:
[0168] First, heat to 460°C at a rate of 3.5°C / min and keep warm for 3h; then heat to 1350°C at a rate of 2°C / min and keep warm for 35min, and finally air cool to room temperature.
[0169] The fracture toughness, impact toughness and flexural strength properties of Examples 1 to 3 and Comparative Examples 1 to 9 were routinely tested, and the test results are as follows;
[0170]
[0171] It can be seen from Comparative Examples 1 to 9 and Examples 1 to 3 that;
[0172] The product of Example 3 has excellent fracture toughness, bending strength and impact toughness, and the three properties can achieve coordinated balanced improvement;
[0173] The test product is placed at -10℃ for 24 hours, then placed at 70℃ for 24 hours, and finally placed in 5% sodium chloride salt spray for 24 hours. The above is one cycle. The cycle treatment is repeated 10 times to test the product's performance stability under cold-heat resistance and high corrosion resistance conditions;
[0174]
[0175] It can be seen from Comparative Examples 1 to 9 and Example 3 that the product of Example 3 has significant performance stability under cold-heat-resistance and high corrosion-resistance conditions;
[0176] The performance of the products showed a significant trend of deterioration when no modifying additives were added to the raw materials of the alloy cutting tools and no conditioning fluid was used for treatment. The synergistic effect of the two was the most significant.
[0177] As the specific operation of sintering improvement treatment is different, the performance of the product also shows a more obvious trend of deterioration;
[0178] The performance of the products showed different degrees of deterioration when the modified additive was not treated with sodium alginate solution, the sodium alginate solution was replaced with a sodium alginate solution with a mass fraction of 5%, the carbon nanotubes dried with S11 were not added to the modified additive, and the additive solution for doping titanium diboride was not added to the modified additive. The performance of the products deteriorated significantly when the additive solution for doping titanium diboride was not added to the modified additive. The modified additive obtained by the specific method of the present invention had the most significant product performance effect. The effects of other methods were not as obvious as those of the present invention.
[0179] In addition, when nano-flaky alumina agent, yttrium nitrate solution and silane coupling agent are not added to the conditioning liquid, the performance of the product tends to deteriorate.
[0180] The performance of the products prepared by different methods, such as modified additives, performance-adjusting liquids and specific sintering improvement treatments, tends to deteriorate. Only by adopting the raw material formula and process of the present invention can the performance effect of the product be most significant.
[0181] The performance of the product has been greatly changed by the addition of titanium diboride, and further research is needed on this:
[0182] The preparation method of the additive solution for doping titanium diboride is as follows:
[0183] Titanium diboride, sodium silicate solution and citric acid were mixed and ball-milled in a weight ratio of 3.5:6:1 at a ball-milling speed of 1500 r / min for 1 h to obtain titanium diboride liquid;
[0184] The nano-neodymium oxide is immersed in a chitosan solution that is 4 times the total amount of the nano-neodymium oxide, and the solution is stirred sufficiently. After the immersion and stirring are completed, the modified nano-neodymium oxide is obtained. The titanium diboride liquid and the modified nano-neodymium oxide are further mixed and stirred in a weight ratio of 4:3 to obtain an additive solution doped with titanium diboride.
[0185] Experimental example 1.
[0186] The only difference from Example 3 is that modified nano-neodymium oxide is not added in the preparation of the additive solution for doping titanium diboride.
[0187] Experimental example 2.
[0188] The only difference from Example 3 is that the modified nano-neodymium oxide is replaced by nano-neodymium oxide.
[0189] Experimental Example 3.
[0190] The only difference from Example 3 is that no titanium diboride liquid is added in the preparation of the additive liquid for doping titanium diboride.
[0191] Experimental Example 4.
[0192] The only difference from Example 3 is that titanium diboride and citric acid are not added to the titanium diboride liquid.
[0193] Experimental Example 5.
[0194] The only difference from Example 3 is that deionized water is used instead of sodium silicate solution in the preparation of the additive solution for adding titanium diboride.
[0195] Taking the product's cold-resistance, heat-resistance and high corrosion resistance performance test as an example, the test was based on the trend results of the effect of the additive liquid mixed with titanium diboride on the product's performance. The test results are as follows:
[0196]
[0197] It can be seen from Experimental Examples 1-5 that when titanium diboride liquid is not added in the preparation of the additive liquid for doping titanium diboride, the performance of the product deteriorates significantly. At the same time, when modified nano-neodymium oxide is not added in the preparation of the additive liquid for doping titanium diboride, the performance effect of the product also has a relatively obvious trend of deterioration. When modified nano-neodymium oxide is replaced by nano-neodymium oxide, titanium diboride and citric acid are not added to the titanium diboride liquid, and deionized water is used instead of sodium silicate solution in the preparation of the additive liquid for doping titanium diboride, the performance of the product has a trend of deterioration. The performance effect of the product obtained by using the specific titanium diboride liquid of the present invention, combined with modified nano-neodymium oxide and a specific raw material formula process to dope titanium diboride additive liquid is the most significant, and the effects of other methods are not as obvious as those of the present invention.
[0198] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0199] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a modified cemented carbide tool, characterized in that: The following steps are involved: Step 1: weigh the raw materials of the alloy tool according to weight: 70-75 parts of WC powder, 5-10 parts of Co powder, 2-5 parts of Ni powder, 2-4 parts of Cr3C2, 4-7 parts of stearic acid, 8-12 parts of paraffin wax, 35-40 parts of ethanol solvent and 4-7 parts of modification additives; Step 2, the raw materials of step 1 are mixed thoroughly, and then ball milled at a ball milling speed of 1000-1500r / min for 2h, and the ball milling is completed to obtain a ball milled material; Step 3, the ball mill is dried and passed through a 100-mesh sieve, and then pressed in a mold to obtain a green body, and then the green body is sprayed with the conditioning liquid until the green body is wetted; Step 4, sintering the product of step 3 to improve the sintering process, and then sintering is completed to obtain a modified cemented carbide tool; The preparation method of the modified additive is: S11: uniformly dispersing the carbon nanotubes in a sufficient amount of 5-7% potassium permanganate solution by ultrasonication at an ultrasonic power of 350-400 W for 20 min, then repeatedly washing with boiling water for 3 times, then filtering and drying; S12: 3-5 parts of sodium alginate powder, 4-7 parts of lanthanum chloride solution and 1-2 parts of phosphate buffer solution are mixed together to obtain a sodium alginate solution; The carbon nanotubes dried in S11 and the sodium alginate solution were stirred at a weight ratio of 2:5, and after the stirring was completed, the mixture was filtered and dried to obtain a carbon nanotube and sodium alginate agent; S13: mixing the carbon nanotubes, sodium alginate agent and the additive solution doped with titanium diboride in a weight ratio of 5:3, and ball milling the mixture at a speed of 1000-1500 r / min for 2 h. After the ball milling is completed, washing with water and drying are performed to obtain a modified additive; The preparation method of the additive solution doped with titanium diboride is as follows: Titanium diboride, sodium silicate solution and citric acid are mixed in a weight ratio of (3-4): (5-7): 1, and the mixture is ball-milled thoroughly at a speed of 1500 r / min for 1 h to obtain titanium diboride liquid; The nano-neodymium oxide is immersed in a chitosan solution with a volume of 3-5 times the total volume of the nano-neodymium oxide, and the solution is stirred sufficiently. After the immersion and stirring are completed, the modified nano-neodymium oxide is obtained. The titanium diboride solution and the modified nano-neodymium oxide are further mixed and stirred in a weight ratio of 4:3 to obtain an additive solution doped with titanium diboride. The preparation method of the conditioning liquid is: S101: irradiating the nano-flaky aluminum oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350 W, and obtaining a nano-flaky aluminum oxide agent after the irradiation is completed; S102: 4-7 parts of nano-flaky alumina agent, 3-5 parts of silane coupling agent, 1-3 parts of 5% by mass sodium dodecylbenzene sulfonate solution and 6-8 parts of 2-4% by mass yttrium nitrate solution are mixed to obtain a performance adjustment solution.
2. The method for preparing a modified cemented carbide tool according to claim 1, characterized in that: The pressing pressure is 100-150 MPa, and the pressing time is 20-30 min; The specific sintering steps of the sintering improvement treatment are: First, keep the temperature at 70-75℃ for 40-50min, then increase the temperature to 450-470℃ at a rate of 2-5℃ / min and keep it for 2-4h; Then heat up to 1050-1100℃ at a rate of 4-7℃ / min, keep warm for 2-3h, then heat up to 1350℃ at a rate of 1-3℃ / min, keep warm for 30-40min, and finally air cool to room temperature.
3. The method for preparing a modified cemented carbide tool according to claim 2, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%; the pH value of the phosphate buffer solution is 5.
5.
4. The method for preparing a modified cemented carbide tool according to claim 3, characterized in that: The stirring speed of the stirring treatment in S12 is 450-550 r / min, the stirring time is 20-30 min, and the stirring temperature is 50-55° C.
5. The method for preparing a modified cemented carbide tool according to claim 4, characterized in that: The mass fraction of the sodium silicate solution is 3-5%; the mass fraction of the chitosan solution is 2-4%; The stirring speed for sufficient immersion stirring is 750-850r / min, and the stirring time is 20-30min; the stirring speed for sufficient mixing stirring is 550-650r / min, and the stirring time is 45-55min.
6. The method for preparing a modified cemented carbide tool according to claim 5, characterized in that: The silane coupling agent is silane coupling agent KH560.
7. A modified cemented carbide tool prepared by the method for preparing a modified cemented carbide tool as claimed in any one of claims 1 to 6.
